2020
DOI: 10.1159/000508546
|View full text |Cite
|
Sign up to set email alerts
|

Attention Deficit/Hyperactivity Disorder and Global Severity Profiles in Treatment-Seeking Patients with Substance Use Disorders

Abstract: Introduction: Comorbid attention deficit/hyperactivity disorder (ADHD) is present in 15-25% of all patients seeking treatment for substance use disorders (SUDs). Some studies suggest that comorbid ADHD increases clinical severity related to SUDs, other psychiatric comorbidities, and social impairment, but could not disentangle their respective influences. Objectives: To investigate whether comorbid adult ADHD in treatment-seeking SUD patients is associated with more severe clinical profiles in these domains as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 51 publications
3
14
1
1
Order By: Relevance
“…Additionally, SUD and nicotine dependence are associated with a negative ADHD outcome [75]. Our findings are in line with Icick [73] and Sanchez [74] on ADHD and SUD with outcome concerns and underline the need for early ADHD detection, diagnosis, and treatment to prevent substance use before escalation to intractable levels.…”
Section: Conclusion and Clinical Implicationssupporting
confidence: 84%
“…Additionally, SUD and nicotine dependence are associated with a negative ADHD outcome [75]. Our findings are in line with Icick [73] and Sanchez [74] on ADHD and SUD with outcome concerns and underline the need for early ADHD detection, diagnosis, and treatment to prevent substance use before escalation to intractable levels.…”
Section: Conclusion and Clinical Implicationssupporting
confidence: 84%
“…We found a prevalence of ADHD of 76% among SUD outpatients. This frequency is considerably higher than others studies among SUD patients where ADHD is found for 15–25% of SUD patients ( 3 , 8 ). It is difficult to date to compare these findings, noticing that our prevalence stands for people who were suspected for ADHD.…”
Section: Discussioncontrasting
confidence: 65%
“…Comorbid ADHD is associated with more severe patterns of SUD ( 8 ), including higher rate of poly-dependence, earlier onset ( 9 ), and cocaine-induced psychotic symptoms ( 10 ). Consequently, diagnosing ADHD in people with SUDs is of utmost importance.…”
Section: Introductionmentioning
confidence: 99%
“…Second, our work provided a categorical evaluation of the association between AUD and ADHD in individuals suffering from BD, without any additional information on frequency and severity of patterns of alcohol use. This issue is particularly important considering that ADHD symptoms might predict the severity of alcohol-related problems [ 57 ] or a polysubstance abuse pattern [ 58 ]. Moreover, an increase in alcohol consumption might be associated with specific features of ADHD, such as attentional bias [ 59 ].…”
Section: Discussionmentioning
confidence: 99%